Biologia reprodutiva de Melastomataceae do Parque Nacional da Serra da Canastra, Minas Gerais - Santos, Ana Paula Milla dos (2008)
Most Melastomataceae species have hermaphrodite flowers with spacial separation of stigma and poricidal anthers, which favours the predominance of xenogamy in this family. Many papers have described the occurrence of self-compatible and apomitic Melastomataceae, but in general, there are few studies yet on the reproductive biology of species with restricted distribution, as common on the campos rupestres. This work verified the reproductive biology of six species of Melastomataceae with distribution restricted to the campos rupestres and related their geographic distribution patterns with the reproductive systems. The reproductive systems was studied by controlled hand pollinations, pollen tube growth analysis, pollen viability, seed germination and initial seedling growth. The relationships between the reproductive systems and geographic distribution of the Melastomataceae was analyzed using the results of this work plus the available data in literature. The controlled hand pollination experiments and pollen tube growth analysis suggest that the species studied, Cambessedesia regnelliana, Miconia angelana, Microlicia inquinans, Svitramia hatschbachii, S. minor and Svitramia sp. were self-compatible, producing viable seeds from self-pollination and without indication of self-incompatibility reactions of pollen tubes along the pistils. The spontaneous self-pollination and production of nectar was observed only in Miconia angelana. The others species, although self-compatible, are dependent on buzz pollination by bees. All the studied species had above 90% pollen viability (estimated by stainability) and were apparently apt to sexual reproduction. The germinability and initial growth of the seeds formed after cross pollination was larger than others treatments, probably due to the greater genetic variability. The exception was M. angelana, in which the germinability and initial growth of seedlings formed by spontaeous self-pollination were significantly larger. The results had confirmed the hypothesis that species with restricted distribution, studied so far, are sexual, mainly selfcompatible (70%). The majority of the studied apomitic species and the self-incompatible ones possesss wide geographic distribution and belongs mainly to the Miconieae tribe.